2014
DOI: 10.1111/ctr.12389
|View full text |Cite
|
Sign up to set email alerts
|

The risk of recurrent IgA nephropathy in a steroid‐free protocol and other modifying immunosuppression

Abstract: Recurrent glomerulonephritis is an important cause of kidney allograft failure. The effect of immunosuppression on recurrent IgA nephropathy (IgAN) is unclear. We analyzed the impact of steroids and other immunosuppression on the risk of recurrent IgAN post-kidney transplantation. Between June 1989 and November 2008, 3311 kidney transplants were performed at our center. IgAN was the primary disease in 124 patients; of these, 75 (60.5%) patients received steroid-based immunosuppression (15 undergoing late stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 19 publications
(25 reference statements)
3
37
1
Order By: Relevance
“…The use of ESW increased from 5% in 1998 to 34% in 2006 . However, existing literature suggests that recurrent IgAN may be more common with these regimens .…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…The use of ESW increased from 5% in 1998 to 34% in 2006 . However, existing literature suggests that recurrent IgAN may be more common with these regimens .…”
Section: Introductionsupporting
confidence: 59%
“…Similarly, Visger et al . observed a significantly higher risk of histologic IgAN recurrence with ESW regimens when compared to steroid continuation regimens (HR 8.59, 95% CI 3.03–24.38; P < 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patient and graft survival was not affected in patients inducted on rATG and maintained on TAC and MMF [44,52]. In a study comprising 124 kidney transplant recipients, of whom 91% were on rATG induction Visger et al, also had the same results as shown by Kuklan [44,53]. Generally in patients where the initial cause of kidney disease is IgA nephropathy, steroid avoidance is not recommended.…”
Section: Steroid Minimization and High Immunological Riskmentioning
confidence: 81%
“…The immunosuppressive and anti-inflammatory actions of corticosteroids appear pertinent to the pathogenic mechanisms in IgAN. Based on data from 27 subjects with biopsy-proven IgAN affecting the transplanted kidney, steroid-free immunosuppression after kidney transplantation was associated with an eightfold increase in the risk of recurrent IgAN 6. Corticosteroids, alone or combined with cytotoxic agents, have been reported to confer renal benefit, although the evidence was not sufficiently robust due to issues related to sample size and/or follow-up duration 7.…”
mentioning
confidence: 99%